Analisis Peran Petugas Apron Movement Control dalam Melakukan Pengawasan dan Pengaturan Lalu Lintas Bandar Udara Internasional Yogyakarta - Damayanti, Putri; Suprapti; Mandrawaty, Vidyana; Prasetyowati (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
In the world of aviation, safety and smooth flight traffic are very important factors. Violations that occur in the apron area are the responsibility of AMC officers in carrying out supervisory and regulatory duties to ensure that all activities run safety and smoothly. So this study aims to observe how the role of AMC in carrying out supervisory and regulatory duties in the apron area. This study uses qualitative research using primary data and secondary data. Data collection techniques are in the form of interviews, observation and documentation. The data analysis technique used in triangulation of techniques and sourches. This study lasted for 1 month from March 1 to March 30, 2025 which was conducted at Yogyakarta Ingternastional Airport. The results of this study indicated that AMC officers have an important role in carrying out supervisory and regulatory duties in flight traffic in order to maintain flight safety and smoothness. There were obstacle found by AMC officers in the work area were able to handle them well because they were equippped with good competence and professional work levels.